Dyschromatosis universalis hereditaria with involvement of palms - Kikkeri Narayanshetty Naveen; U S Dinesh (Wolters Kluwer Medknow Publications, 2014)
Dyschromatosis universalis hereditaria is a rare genodermatosis characterized by hyper- and hypopigmented macules in a reticulate pattern. Here, we present a case of DUH with involvement of the palms.